Cuproptosis-Related Risk Score Predicts Prognosis and Characterizes the Tumor Microenvironment in Hepatocellular Carcinoma - Zhang, Zhen; Zeng, Xiangyang; Wu, Yinghua; Liu, Yang; Zhang, Xi; Song, Zewen (Frontiers in Immunology, 2022)
Aims: Cuproptosis is a recently identified form of programmed cell death; however, its role in hepatocellular carcinoma (HCC) remains unclear. Methods: A set of bioinformatic tools was integrated to analyze the expression and prognostic significance of Ferredoxin 1 (FDX1), the key regulator of cuproptosis. A cuproptosis-related risk score (CRRS) was developed via correlation analyses, least absolute shrinkage and selection operator (LASSO) Cox regression and multivariate Cox regression. The metabolistic features, mutation signatures and immune profile of CRRS-classified HCC patients were investigated, and the role of CRRS in the therapy guidance was analyzed. Results: FDX1 were significantly down-regulated in HCC and its high expression was associated with longer survival time. HCC patients in the high-CRRS group showed a significantly lower overall survival (OS) and enriched in cancer-related pathways. Mutation analyses revealed that the high-CRRS HCC patients had high mutational frequency of some tumor suppressors like tumor protein P53 (TP53) and BRCA1 associated protein 1 (BAP1), and low frequency of catenin beta 1 (CTNNB1). Besides, HCC patients with high CRRS showed an increase of pro-tumor immune infiltrates and high expression of immune checkpoints. Moreover, the area under curve (AUC) value of CRRS in predicting the efficiency of sorafenib and the non-responsiveness of transcatheter arterial chemoembolization (TACE) in HCC patients reached 0.877 and 0.764, respectively. Significance: The cuproptosis related signature is helpful for prognostic prediction and in guiding treatment for HCC patients.